Estudo do Comportamento de Variáveis de Solo Utilizando o Modelo Noah para uma Cultura de Arroz Irrigado - Timm, Andréa (2013)
This study aims to evaluate the performance of the land surface model Noah by simulating soil data and compare them with observed data in a region with rice in southern Brazil. From the results, it is observed that the Noah model needs adjustments, especially when analyzing the parameter volumetric soil moisture.